Web-Based Non-Profit Organization Accounting Information System Reconstruction - Ivonne Helena Putong; Antonius Manginsela; Joseph Nugraha Tangon (AKRUAL: JURNAL AKUNTANSI, 2023)
Abstract One of the largest non-profit organizations in North Sulawesi is the Minahasa Evangelical Christian Church (GMIM). Although it’s not business-oriented, church administrators are required to make financial reports as an accountability to the congregation and donors. There are several obstacles in financial management. Financial management is held by the treasurer assisted by church employees who do not always have an accounting education background. Working as a treasurer not as a full-time employee but setting aside time from routine activities to manage church finances. So far, financial administration and reporting have been made manually using Microsoft Excel. As a result, processing time becomes longer, requires a lot of energy and has the potential for errors to occur. This collaborative research aims to provide a solution by reconstructing the church's accounting information system and then making it in one application. The church's accounting system uses a cash basis, so this study covers the cash receipts and disbursements system. This research is included in the type of research and development (research and development), namely a research approach to produce a new product. The church accounting information system is designed to follow the applicable rules, namely the 2021 GMIM Synod Church Administration and the GMIM Treasury Supervision and Governance Service Guidelines that 1,049 GMIM Congregants must obey. The results of the reconstruction are made in the Indah GMIM application to make it easier for users to generate church financial reports. Faster processing time, reports more precise. Decision making is faster because reports are usually done waiting for free time from managers because they still use the manual method with Ms. Excel, but with the INDAH application it can be done anytime and anywhere